The relatinship between social support and health related quality of life: Systematic review - Sarla, E.; Lambrinou, Ekaterini; Kalokairinou, A.; Sourtzi P., Panayota (My University, 2016)
Social networks usually affect the health status and self-esteem of groups and individuals positively. The higher the degree of social networking, the higher the influence. The impact on older people is of particular interest. AIM: This systematic review examines whether perceived social support by older people receive from various groups in their life is related to or affects their health and quality of life. METHODS: The electronic databases PubMed, Scopus, Cochrane were searched with keywords “social support”, “perceived social support”, “health related quality of life”, “older people” in all possible combinations using the operator “and”. Inclusion and exclusion criteria were used. All studies which referred to social support and health related quality of life of older people were included in the review. To assess the methodological quality of the studies we used Joanna Briggs Institute’s critical appraisal checklist. RESULTS: Twenty-two studies were included in this systematic review. Social support and health related quality of life were measured by using different tools for measuring social support and health. In the majority of studies social support positively influences all aspects of health and quality of life. In some studies, social support has a positive and statistically significant relationship with health regardless of the type of social network. CONCLUSION: Different types of social relationships affect functionality of older people differently. A large social support network that extends beyond the family is a key factor for better overall health of older people.
Keywords: Elderly; Quality of life; Social support